Forgetting Items : The Social Experience of Alzheimer's Disease - Brossard, Baptiste, 1985- (Book collections on Project MUSE., 2019)
Alzheimer's disease has not only profound medical consequences for the individual experiencing it but a life-changing impact on those around them. From the moment a person is suspected to be suffering from Alzheimer's or another form of dementia, the interactions they encounter progressively change. Forgetting Items focuses on that social experience of Alzheimer's, delineating the ways disease symptoms manifest and are understood through the interactions between patients and the people around them.